STRATEGI GURU MENERAPKAN METODE MUSICAL MNEMONIC INTEGRATION UNTUK DAYA INGAT AUDITORI PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Fajar Agustian; Syahrial; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the teacher's strategy in planning and implementing the Musical Mnemonic Integration (MMI) method to improve the auditory memory of students in Indonesian language learning at SDN 80/I Muara Bulian. This research uses a qualitative approach with a phenomenological design. Data collection techniques included in-depth interviews with the third-grade teacher and principal, participant observation of the learning process, and documentation of teaching devices. The results showed that the teacher's strategy was carried out through three systematic stages: planning by modifying material into song lyrics, implementation by utilizing rhythms and melodies as encoding tools, and evaluation through direct observation of student recall. The findings indicate that the integration of music effectively increases students' focus and enthusiasm, helping them transfer information into long-term memory. Despite constraints such as limited musical instruments and time, teacher creativity and school support are key to the successful optimization of students' auditory memory.